Influence of sequential tillage and residue management practices on soil and root parameters in soybean (Glycine max) - wheat (Triticum aestivum) cropping system - KARUNAKARAN, V; BEHERA, U K (The Indian Journal of Agricultural Sciences, 2015)
A field study was conducted in 2009-10 and 2010-11 at Indian Agricultural Research Institute, New Delhi to assess the effect of sequential tillage and crop establishment and residue management practices on soil health and root parameters in soybean [Glycine max (L.) Merr.] - wheat (Triticum aestivum L.) cropping system. The results pertaining to the experiments at the end of the two year study revealed that most of the soil properties except infiltration rate and microbial biomass carbon (MBC); and root parameters of both crops except root length density (RLD) and average root diameter of wheat were non-significant by the sequential tillage and crop establishment treatments. Unlike sequential tillage and crop establishment techniques, all soil properties except bulk density, pH, EC and root parameters of both soybean and wheat responded significantly to the residue management practices. The infiltration rate was significantly higher with skipping the sequence of CT-Flat by ZT-Flat. Skipping the sequence of CT-Flat and bed with ZT-Flat and bed recorded higher soil mean weight diameter (MWD) and grand mean diameter (GMD) at 0- 10 cm soil depth than the counterpart by skipping of ZT-Flat and bed with CT-Flat and bed. The percentage of soil macro-aggregate was high by skipping ZT-Flat and bed with CT-flat and bed at all depths while the reverse was exhibited in case of percentage soil micro-aggregates by skipping CT-Flat and bed with ZT-Flat and bed. By skipping CT-flat and bed with ZT-flat and bed significantly higher soil MBC was recorded than the counterpart skipping tillage treatments. The same significant trend was also exhibited for soil MBC with residue management treatments, where the wheat + soybean residue application recorded 20.90 % higher than the control. Root parameters like RLD, root surface area (RSA), root volume density (RVD), average root diameter (ARD) in soybean while these were partly non-significant (RSD and RVD) in wheat with the sequential tillage and crop establishment treatments, whereas the residue management practices significantly influenced the root parameters of both the crops. Among the residue management practices, wheat + soybean residue obtained higher RLD (2.57 and 1.03 cm/cm3); RSA (0.79 and 0.32 cm2/cm3); RVD (18.11 and 7.46 Ã— 10-3 cm3/cm3) and average root diameter (1.04 and 0.85 mm) both in soybean and wheat crops than rest of the treatments. Thus, impact of short-term zero tillage is short lived for favourable soil health and root parameters when skipping with conventional tillage.